As representações de espaços urbanos americanos presente nas fotografias de mulheres de Alice Brill e Vivian Maier, realizadas na década de 1950 - Gois, Ana Elyze Santos Martins de (2022)
This research is about the representations of urban spaces in the cities of São Paulo and New York produced by photographers Alice Brill and Vivian Maier in photographs of women in the 1950s. and Vivian Maier, the representations of these urban spaces in photographs of women made by them. Affiliating myself with Stuart Hall's (2016) studies of representation and the image analysis methodology of Ana Maria Mauad (1991; 2008) and Zita Possamai (2005), I go through digital photographs of the two photographers. The study uses the collections of public and private guarding institutions, accessing them digitally and mediated by the documentary arrangements of these institutions. Thus, with the research, through documental and image analysis, as well as theoretical and bibliographic articulation, I proposed to think about the relationships between the photographic production of women and the representation of women in photography, both practices in public and constituent spaces. of the representation that one has of it. Three narrative entries were proposed for the research in order to deepen the photographers' gaze towards space, as well as condense the analyzes carried out, they were: the city, in which with the use of maps, routes and walks, I analyzed the appropriation of spaces from the cities of São Paulo and New York that Alice and Vivian, respectively, made; the second road was the analysis of the body, of how it relates to itself and to others, permeated by photography; the third discusses how the body and the city are related in Alice and Vivian's photographs, how sociabilities between women were perceived and how women used strategies and ways of occupying cities, which for the most part had not been designed to the presence and occupation with women's bodies. In this way, it is concluded that the urban spaces represented were used and constituted ways of being and occupying these spaces by women, so that the represented spaces were produced due to the presence of women in them, whether they were the ones photographed or the photographers responsible for image production.